2021
DOI: 10.21037/gs.2020.03.16
|View full text |Cite
|
Sign up to set email alerts
|

Alternative flaps in autologous breast reconstruction

Abstract: The gold standard for autologous reconstruction in the post-mastectomy patient remains the deep inferior epigastric artery perforator flap, although many women may not be candidates for abdominally based free tissue transfer. In this scenario, there are several other donor site options based from the thigh (transverse and diagonal upper gracilis flaps, profunda artery perforator flap, lateral thigh flap) and trunk (lumbar artery perforator flap, superior and inferior gluteal artery perforator flaps). This stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 75 publications
0
28
0
7
Order By: Relevance
“…The dissection of the vPAP will not be as anterior and has a higher chance of sparing the lymphatic drainage. 20,21 We found that the dominant perforator is located at a mean distance of 1.98 and 1.26 cm (on imaging and cadaveric dissection, respectively) from the posterior border of the gracilis. Furthermore, distal perforators were found in a slightly more anterior location, suggesting that vertical flap design may be shifted slightly anteriorly when centered on these vessels.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…The dissection of the vPAP will not be as anterior and has a higher chance of sparing the lymphatic drainage. 20,21 We found that the dominant perforator is located at a mean distance of 1.98 and 1.26 cm (on imaging and cadaveric dissection, respectively) from the posterior border of the gracilis. Furthermore, distal perforators were found in a slightly more anterior location, suggesting that vertical flap design may be shifted slightly anteriorly when centered on these vessels.…”
Section: Discussionmentioning
confidence: 81%
“…The dissection of the vPAP will not be as anterior and has a higher chance of sparing the lymphatic drainage. 20 21…”
Section: Discussionmentioning
confidence: 99%
“…Compared to other popular and most commonly used alternatives to the DIEP flap for autologous breast reconstruction such as the lumbar artery perforator (LAP) flap, the superior gluteal artery perforator (SGAP) flap or the fasciocutaneous infragluteal free flap (FCI) flap, the TMG flap offers a comparable size and a similar complication profile, the mean pedicle length is significantly shorter though [36][37][38]. An overview of the common used free flaps and their detailed characteristics is shown in Table 5 [21,23,34,39,40].…”
Section: Discussionmentioning
confidence: 99%
“…The gold standard for autologous reconstruction in the post-mastectomy patient remains the DIEAP flap, although many women may not be candidates for abdominally based free tissue transfer. In this scenario, there are several other donor site options on the thigh (transverse and diagonal upper gracilis flaps, profunda artery perforator flap, lateral thigh flap) and trunk (lumbar artery perforator flap, superior and inferior gluteal artery perforator flaps) [ 38 ], [ 39 ].…”
Section: Autologous Breast Reconstructionmentioning
confidence: 99%